Reorganization of Brain Functional Connectivity Network and Vision Restoration Following Combined tACS-tDCS Treatment After Occipital Stroke - Xu, Jiahua; Wu, Zheng; Nürnberger, Andreas; Sabel, Bernhard A. (Frontiers in Neurology, 2021)
Objective: Non-invasive brain stimulation (NIBS) is already know to improve visual field functions in patients with optic nerve damage as it partially restores the organization of brain functional connectivity networks (FCN). However, because little is known if NIBS is effective also following brain damage, we now studied the correlation between visual field recovery and FCN reorganization in stroke patients with central visual pathway damage. Method: In a controlled, exploratory trial, 24 patients with hemianopia were randomly assigned to one of three brain stimulation groups: tDCS/ tACS (ACDC); Sham tDCS/ tACS (AC); sham tDCS/ Sham tACS (SHAM) which were compared to age-matched controls (n=24). Resting-state EEG was collected at baseline, after 10 days of stimulation, and at two months follow-up. EEG recordings were analyzed for FCN measures using graph theory parameters, and FCN small-worldness network and long pairwise coherence parameter alterations were then correlated with visual field performance. Result: ACDC enhanced alpha band FCN strength in the superior occipital lobe of the lesioned hemisphere at follow-up. A negative correlation (r=-0.80) was found between the intact visual field size and characteristic path length (CPL) after ACDC with a trend of decreased alpha-band centrality of the intact middle occipital cortex. ACDC also significantly decreased delta band coherence between the lesion and the intact occipital lobe, and coherence was enhanced between the occipital and temporal lobe of the intact hemisphere in the low beta band. Responders showed significantly higher strength in the low alpha band at follow-up in the intact lingual and calcarine cortex, and in the superior occipital region of the lesioned hemisphere. Conclusion: While ACDC decreases delta band coherence between intact and damaged occipital brain areas indicating inhibition of low-frequency neural oscillations, ACDC increased FCN connectivity between the occipital and temporal lobe in the intact hemisphere. When taken together with the lower global clustering coefficient in responders, these findings suggest that FCN reorganization (here induced by NIBS) is adaptive in stroke, leading to greater efficiency, where the FCN requires fewer connections for visual processing.